SELF CONFIDENCE SISWA DALAM MEMECAHKAN SOAL SERUPA PISA BERKONTEN CHANGES AND RELATIONSHIPS - Khasmawati, Hanik; Waluya, St Budi; Asikin, Mohammad (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2022)
The purpose of the study was to determine student’s self confidence in solving problems similar to PISA with the content of change and relationship and the selected material, namely SPLDV. This research is a qualitative descriptive. The population of this research was class VIII MTs NU Nurul Huda with a sample of class VIII-B consisting of 34 students. Data collection in this research includes observations, questionnaires, written tests, interviews and documentation. The data analysis process including data reduction activities, data presentation and data collection using triangulation techniques. The results of this study indicate that students who have high self confidence have the ability to solve problems similar to PISA more than students who have moderate or low self confidence. Students who have moderate self confidence have the ability to solve problems similar to PISA more than students who have low self confidence.